Daya Anagata Nusantara: An Analysis of Investment Opportunities in Danantara for National Economic Growth - Musriani, Musriani; Difinubun, Yusron; Prastiwi, Rahel (Amkop Management Accounting Review (AMAR), 2025)
This study aims to identify investment opportunities in Danantara for national economic growth. It uses qualitative secondary data research methods, employing the IFAS, EFAS, and SWOT approaches to facilitate data collection using NVivo software and literature review.  SWOT analysis is a tool for evaluating the strengths, weaknesses, opportunities, and threats that can affect Danantara's success, as well as for identifying growth potential through strategic partnerships, innovation, and policy changes that support Danantara's competitiveness. The results of the study show that the news coverage of Danantara involved 48 male journalists and 43 female journalists, with a relatively diverse distribution of locations, with dominance in Jakarta, followed by other major cities such as Bandung, Surabaya, and Yogyakarta, which showed gender balance. In contrast, several regions remained dominated by one gender. From an investment perspective, Danantara is in quadrant 1 (progressive) with dominant strengths (score of 3.59) as a state-owned superholding company, a symbol of digital economic transformation, an instrument of national development, and a catalyst for inclusive economic growth, supported by significant opportunities (score of 3.30) to strengthen economic independence, global competitiveness, and sustainable development. However, weaknesses (score of 2.09) and threats (score of 2.30) remain significant, particularly regarding governance, regulation, and the risk of politicisation, which could undermine public trust. Thus, the success of Danantara is highly dependent on strengthening modern governance, transparency, accountability, and targeted investment strategies through digital transformation, global investor confidence, integration of state assets, infrastructure development, industrialisation, renewable energy, and downstreaming of natural resources, so that it can become an effective state instrument to strengthen economic independence, increase public trust, and align development towards the Indonesia Emas 2045 vision.